Type specimens of “insectivoran” mammals at the Museum für Naturkunde, Berlin - Turni, Hendrik; Hutterer, Rainer; Asher, Robert (Zootaxa, 2007)
The collection of the Zoological Museum of the Humboldt-University Berlin holds approximately 2,000 mammal type specimens. No catalogue has yet been published. Here, we present a type catalogue of the non-monophyletic group “Insectivora” containing the Erinaceidae (hedgehogs), Soricidae (shrews), Talpidae (moles), Solenodontidae (solenodons), and Chrysochloridae (golden moles). We checked the present nomenclatural and taxonomic status of each (referred) type specimen. We registered 33 holotypes, 69 syntypes and 13 paratypes (of which 17 represent subspecies and 3 are missing). We reidentified two original specimens of Khster’s Sorex pachyurus, now Crocidura pachyura, which is a senior name for Crocidura ichnusae. Lectotypes are designated for Solenodon cubanus, Sorex pachyurus, and Myosorex preussi.